Axonal degeneration is regulated by the apoptotic machinery or a NAD+-sensitive pathway in insects and mammals. - Schoenmann, Z.; Assa-Kunik, E.; Tiomny, S.; Minis, A.; Haklai-Topper, L.; Arama, E.; Yaron, A. (Journal of Neuroscience, 2010)
Selective degeneration of neuronal projections and neurite pruning are critical for establishment and maintenance of functional neural circuits in both insects and mammals. However, the molecular mechanisms that govern developmental neurite pruning versus injury-induced neurite degeneration are still mostly unclear. Here, we show that the effector caspases 6 and 3 are both expressed within axons and that, on trophic deprivation, they exhibit distinct modes of activation. Surprisingly, inhibition of caspases is not sufficient for axonal protection and a parallel modulation of a NAD(+)-sensitive pathway is required. The proapoptotic protein BAX is a key element in both pathways as its genetic ablation protected sensory axons against developmental degeneration both in vitro and in vivo. Last, we demonstrate that both pathways are also involved in developmental dendritic pruning in Drosophila. More specifically, the mouse Wld(S) (Wallerian degeneration slow) protein, which is mainly composed of the full-length sequence of the NAD(+) biosynthetic Nmnat1 enzyme, can suppress dendritic pruning in C4da (class IV dendritic arborization) sensory neurons in parallel to the fly effector caspases. These findings indicate that two distinct autodestruction pathways act separately or in concert to regulate developmental neurite pruning.